Sosialisasi Perancangan Antarmuka Aplikasi Web Penjadwalan Konten Sosial Media - I Wayan Restama Yasa; Anak Agung Istri Ngurah Eka Karyawati; Cokorda Rai Adi Pramartha (Jurusan Informatika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2026)
The manual scheduling of social media content using Microsoft Excel causes inaccuracies, coordination difficulties, and information delays for the creative team at Ramerame.co.id. To address these issues, a web-based social media content scheduling application interface was designed to facilitate real-time collaboration and more efficient schedule management. The interface design was developed using Figma with an interactive and user-friendly approach, resulting in an intuitive, collaborative, and easily accessible display for the creative team. This design enables structured, real-time, and collaborative planning, recording, and monitoring of social media content within an integrated platform. Evaluation results of the design show that the application interface has the potential to improve the efficiency of the creative team and reduce miscommunication in content planning. Although it is still in the design stage, further development and implementation of this interface are expected to realize more effective social media content management in the future.